Pengaruh Pendidikan Kesehatan Makanan Jajanan terhadap Pengetahuan, Sikap dan Perilaku dalam Pemilihan Makanan Jajanan pada Siswa Sekolah Dasar Negeri 01 Madegondo Grogol - Aderita - Poltekkes Bhakti Mulia, Novi Indah (IJMS - Indonesian Journal on Medical Science, 2020)
Abstract: Snack food is closely related to school-age children. Research result from the Indonesian Consumers Foundation (YLKI) stated that 98.7% of elementary school children enjoy consuming snacks at school. However, problems often arise from the use of hazardous substances in food, the behavior of children consuming unsafe snacks and the lack of parental supervision of childrens snack behavior. So a strategy is needed to determine the selection of healthy snacks, one of which is by providing health education. This study aims to analyze the effect of health education on increasing knowledge, attitude, and behavioral changes in the selection of snack foods in elementary school 01 Madegondo Grogol. The research design used a pre-post experiment with a pre-test and post-test design approach. The research was conducted in September-November 2019 at elementary school 01 Madegondo Grogol. The number of research subjects with a fixed exposure sampling subject technique. The technique of collecting data with a questionnaire. Data analysis using t-test. The result of this study are: based on the t-test carried out on the knowledge variable, the value of p = 0.000 is obtained, the value of the attitude variable is p=0.033, and the value for the behavior variable is p = 0.000. The results show that there is an effect of health education on increasing knowledge, attitude and behavior changes in the selection of healthy snack food which are proven to be statistically significant. Cooperation between the school and parent is needed to encourage children to behave in healthy lives.Keyword: Health Education, Knowledge, Attitude, Behaviour, Food Snack. Abstrak: Makanan jajanan erat kaitannya dengan anak usia sekolah. Hasil penelitian Yayasan Lembaga Konsumen Indonesia (YLKI) menyebutkan bahwa 98,7% anak Sekolah Dasar (SD) senang mengkonsumsi jajanan di sekolah. Namun seringkali timbul masalah penggunaan zat-zat berbahaya dalam makanan, perilaku anak mengkonsumsi jajanan yang tidak aman dan kurangnya pengawasan orang tua terhadap perilaku jajan anak. Sehingga diperlukan strategi untuk mengetahui pemilihan jajanan yang sehat, salah satunya dengan upaya memberikan pendidikan kesehatan. Penelitian ini bertujuan untuk menganalisis pengaruh pendidikan kesehatan terhadap peningkatan pengetahuan, sikap, dan perubahan perilaku dalam pemilihan makanan jajanan di Sekolah Dasar Negeri (SDN) 01 Madegondo Grogol. Desain penelitian menggunakan pre-post eksperimen dengan pendekatan pre test-post test desain. Penelitian dilaksanakan pada September – November 2019 di SDN 01 Madegondo. Jumlah subjek penelitian yang digunakan sejumlah 50 subjek dengan teknik pengambilan subjek fixed exposure sampling. Teknik pengumpulan data dengan kuesioner. Analisis data menggunakan t test. Hasil penelitian ini adalah: berdasarkan uji t yang dilakukan pada variable pengetahuan didapatkan nilai p = 0.000, pada variabel sikap didapatkan nilai p = 0.033, dan pada variabel perilaku didapatkan nilai p = 0.000. Hasil menunjukkan bahwa terdapat pengaruh pendidikan kesehatan terhadap peningkatan pengetahuan, sikap dan perubahan perilaku dalam pemilihan makanan jajanan sehat yang terbukti secara statistic signifikan. Kerjasama antara pihak sekolah dan orang tua diperlukan untuk mendorong anak berperilaku hidup sehat. Kata Kunci: Pendidikan Kesehatan, Pengetahuan, Sikap, Perilaku, Makanan Jajanan